Design and Construction of Additional Security Device for House Door Using Arduino Uno Based on Short Message Service - Yuan Reski Wara; Tri Wahyu Oktaviana Putri (Journal of Electrical, Electronic, Information, and Communication Technology, 2021)
Security is a very important aspect of a house. The level of protection and comfort of the house certainly cannot be separated from how good the security system of the house is. The door is used for the main entrance and exit of the house. When the owner of the house is inside, the door can be locked from the inside with the addition of a slop lock on the door. However, if the owner of the house leaves, the door is only locked using a regular key without any additional keys on the inside of the door. So that the door of the house can be opened only by "lockpick" by an irresponsible person. Such problems can be prevented by installing additional security devices on the door of the house that can be controlled to lock the inside of the door and can provide early warning to homeowners through SMS (Short Message Service) notifications on cell phones. The components used in this system are Arduino Uno microcontroller, Servo Motor, Vibration Sensor (SW-420), Buzzer, Magnetic Switch MC-38, and GSM SIM800L V2. The prototype worked well and reach the research’s objective.